2022
DOI: 10.3389/fpsyg.2022.939661
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between perceived classroom climate and academic performance among English-major teacher education students in Guangxi, China: The mediating role of student engagement

Abstract: The academic performance of teacher education students predicts their future career development and it is also a significant factor related to their future students’ academic performance. However, little is known about the associations between perceived classroom climate, student engagement and academic performance, especially for English-major teacher education students. This study was to examine English-major teacher education students’ academic performance in relation to perceived classroom climate, student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Research has demonstrated that motivation and self-regulation are positively correlated with success, performance, and fulfillment in online learning contexts (Ma & Wei, 2022). Students who are highly motivated and engaged in their studies tend to participate actively in class and complete assignments with greater alacrity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that motivation and self-regulation are positively correlated with success, performance, and fulfillment in online learning contexts (Ma & Wei, 2022). Students who are highly motivated and engaged in their studies tend to participate actively in class and complete assignments with greater alacrity.…”
Section: Introductionmentioning
confidence: 99%
“…For students, online learning differs from classroom learning in that it necessitates a high degree of self‐direction, self‐confidence, and self‐motivation. Research has demonstrated that motivation and self‐regulation are positively correlated with success, performance, and fulfillment in online learning contexts (Ma & Wei, 2022). Students who are highly motivated and engaged in their studies tend to participate actively in class and complete assignments with greater alacrity.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered, along with social identification, a basic element for improving student performance by acquiring and practicing SEL [ 4 ] and for ensuring success in life [ 15 ]. The creation of a positive school climate and an increased level of student involvement is also associated with increased academic performance among students [ 16 , 17 ]. However, it must be remembered that the school environment differs between schools, which can lead to a different vision of the school reality as each school’s reality is unique [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, learner engagement and motivation can result in improving their performance and achievement and increasing their satisfaction (Ma & Wei, 2022;Martin & Bolliger, 2018;Palos et al, 2019). Jang et al (2010) recognize the importance of engagement for student learning.…”
Section: Introductionmentioning
confidence: 99%